Numerical simulation of the hepatic circulation. - van der Plaats, A; 't Hart, N; Verkerke, G; Leuvenink, H; Verdonck, P; Ploeg, R; Rakhorst, G (2004)
Availability of donor livers and the relatively short preservation time limit the success of liver transplantation. The use of hypothermic machine perfusion could pave the way for expansion of the donor pool. To better define optimal settings of such a device, the feasibility of using a numerical simulation model of the hepatic circulation is determined. Hemodynamics in the hepatic arterial, portal venous and hepatic venous compartments of the hepatic vascular tree was modelled using an electrical analogue. Calculated pressure and flow profiles throughout the liver were in accordance with physiologic profiles in the total circulatory system. Comparison of calculated flow values with normal control values showed a discrepancy that was explained by inaccurate diameter input data. Until more precise methods for determining vascular dimensions become available, redefining vessel diameter makes the simulation model perfectly suitable for predicting influences of temperature and/or viscosity on hepatic hemodynamics and is thereby an excellent tool in defining optimal settings for our hypothermic liver perfusion system.